IMPLEMENTASI VIDEO PEMBELAJARAN BERBASIS YOUTUBE MATERI KALIMAT LANGSUNG DAN KALIMAT TIDAK LANGSUNG UNTUK SISWA SEKOLAH DASAR - Maghfirah; Siti Mayang Sari; Irfandi (STKIP Subang, 2026)
This study aims to describe the implementation of YouTube-based learning videos in teaching direct and indirect speech to elementary school students. The research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving one classroom teacher and 21 fifth-grade students in an elementary school setting. The data analysis technique was conducted through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that YouTube-based learning videos have been implemented as a supporting medium, particularly in teaching direct and indirect speech. The use of YouTube-based media makes the learning process more engaging and effective in Indonesian language instruction.